2011
DOI: 10.1016/j.jenvman.2011.03.023
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying the influence of environmental and water conservation attitudes on household end use water consumption

Abstract: Within the research field of urban water demand management, understanding the link between environmental and water conservation attitudes and observed end use water consumption has been limited. Through a mixed method research design incorporating field-based smart metering technology and questionnaire surveys, this paper reveals the relationship between environmental and water conservation attitudes and a domestic water end use break down for 132 detached households located in Gold Coast city, Australia. Usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
204
0
8

Year Published

2011
2011
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 324 publications
(227 citation statements)
references
References 27 publications
7
204
0
8
Order By: Relevance
“…Many studies have confirmed that water conservation attitudes and behavior are closely related [23,32]. Some studies have revealed that residents with positive attitudes may not always exhibit positive behavior [33].…”
Section: Discussionmentioning
confidence: 97%
“…Many studies have confirmed that water conservation attitudes and behavior are closely related [23,32]. Some studies have revealed that residents with positive attitudes may not always exhibit positive behavior [33].…”
Section: Discussionmentioning
confidence: 97%
“…Usually technological improvements are long-term investments, whereas behavioral modification can occur in the short-run-as a reaction of a temporal price increase or supply rationing-but also can react to educational campaigns or increased environmental consciousness [Gilg and Barr, 2006;Willis et al, 2011] as either a short or long-term strategy…”
Section: Conservation Actionsmentioning
confidence: 99%
“…Environmental concerns, financial considerations, and household demographics are the main factors influencing consumers' adoption of water-efficient technologies [14,19,24,25,32,33]. Consumers who are more environmentally conscious are more likely to take actions to conserve water, including purchasing water-efficient products [19,25].…”
Section: Introductionmentioning
confidence: 99%